Exploring the Orchid Flora of Montenegro: Ten Newly Identified Taxa - Boris Đoka Radak; Jovan Milan Peškanov; Bojana Slavenko Bokić; Goran Timča Anačkov (Diversity)
Montenegro, with approximately 3600 vascular plant taxa, represents one of the floristic diversity centers of the Balkan Peninsula and the Mediterranean region. According to our current knowledge, about 80 to 100 orchids, including species, subspecies, and hybrids, occur in this country. To refine the understanding of orchid diversity in Montenegro, extensive fieldwork and herbarium revisions were conducted. As a result, ten new orchid taxa were recorded in Montenegro for the first time. These include Epipactis helleborine subsp. distans, E. leptochila subsp. neglecta, Gymnadenia densiflora, Neotinea ustulata var. aestivalis, Ophrys archipelagi, O. grammica, and Pseudorchis albida subsp. tricuspis. In addition, one intergeneric hybrid, ×Serapicamptis rousii, and two intrageneric, Anacamptis ×nicodemi and A. ×olida, were found. Distribution data, ecological preferences, and population sizes for newly registered taxa in Montenegro have been given. This study underscores the great potential of the flora of Montenegro for discoveries in the orchid world.